GE_GERICHTE P/13832/2006 vom 10. März 2008 - GE Cour de justice (2008)
; PRÉSOMPTION D'INNOCENCE ; MOYEN DE PREUVE ; TÉMOIN À DÉCHARGE | CPP.107A; CP.49; CP.106; CP.34.2; LCR.90.1; LCR.92.1.90.1 LCR.91 LCR.92.1